2022
DOI: 10.1007/s00128-022-03576-6
|View full text |Cite
|
Sign up to set email alerts
|

A First Record of Organochlorine Pesticides in Barn Owls (Tyto alba) from Portugal: Assessing Trends from Variation in Feather and Liver Concentrations

Abstract: We evaluated feathers as a non-destructive biomonitoring tool documenting organochlorine pesticides (OCP) in liver and checked possible trends in pesticide use in two areas based on OCP concentrations in barn owls (Tyto alba). We measured the concentrations of 16 OCP in 15 primary feathers and 15 livers from barn owl carcasses collected on roadsides in Tagus Valley and Évora regions, south Portugal. Total OCP mean concentration was 8 120 ng g −1 in feathers and 178 ng g −1 in livers. All compounds were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…2,4′‐dichlorodiphenyldichlorethane was detected in 8% to 29% of the analyzed birds at concentrations from 0.06 to 2.58 ng/g wet weight, and other DDT isomers were seldom detected (Table 1), with 4,4′‐DDT never being detected, indicating that it has not been used over the last decades, coinciding with the Stockholm Convention (2019) phase out of this compound. Our results are consistent with those of Roque et al (2022), who found 4,4′‐DDE as the most prevalent OCP in livers from road‐killed barn owls in Portugal at mean concentrations from 1.93 to 162 ng/g wet weight, lower that the ones found in barn owls in the present study, which were from 2.19 to 636 ng/g wet weight. Also, 4,4′‐DDE was the main OCP detected in livers from 18 diurnal birds of prey in Spain (van Drooge et al, 2008) and in white‐tailed eagles ( Haliaeetus albicilla ) in Germany (Badry et al, 2022).…”
Section: Resultssupporting
confidence: 93%
“…2,4′‐dichlorodiphenyldichlorethane was detected in 8% to 29% of the analyzed birds at concentrations from 0.06 to 2.58 ng/g wet weight, and other DDT isomers were seldom detected (Table 1), with 4,4′‐DDT never being detected, indicating that it has not been used over the last decades, coinciding with the Stockholm Convention (2019) phase out of this compound. Our results are consistent with those of Roque et al (2022), who found 4,4′‐DDE as the most prevalent OCP in livers from road‐killed barn owls in Portugal at mean concentrations from 1.93 to 162 ng/g wet weight, lower that the ones found in barn owls in the present study, which were from 2.19 to 636 ng/g wet weight. Also, 4,4′‐DDE was the main OCP detected in livers from 18 diurnal birds of prey in Spain (van Drooge et al, 2008) and in white‐tailed eagles ( Haliaeetus albicilla ) in Germany (Badry et al, 2022).…”
Section: Resultssupporting
confidence: 93%
“…Total analysis time was 47.067 min” [ 288 ] Penguin tissues 31 2.2–4.6 Sur: 53–136; spike: 113; SRM: 130 GC-ECD: “The column oven was programmed for an initial temperature of 100 °C for 1 min and a rate of 5 °C/min to 140 °C, then held for 1 min at 140 °C, ramped to 250 °C at a rate of 1.5 °C/min, held for 1 min and finally increased at a rate of 10 °C/min to 300 °C and held for 5 min” [ 378 ] Blood of penguins, short-tailedshearwaters 14 MDL: 0.04–0.95 MQL: 0.12–3.2 82–115 GC-MS/MS: “The initial inlet temperature was 90 °C for 0.1 min before ramping to 325 °C at 900 °C/min. The oven temperature was 50 °C for 1 min and then ramped to 320 °C at 25 °C/min with a hold time of 4 min” [ 22 ] Eagle-owl feathers 12 0.05–0.10 Internal: 71-92 <30 GC-MS: “Splitless, the temperature of the DB-5 column was programmed from 90 °C, kept for 1.5 min, then increased with 15 °C/min to 310 °C, kept for 15 min” [ 73 ] Feathers, liver of owl 16 0.03–0.54 46-146 (feathers) 86 146 (liver) GC-MS [ 379 ] Blood cell and feather of Antarctic petrels 5 0.00172–0.305; 0.00517–1.016 45–104 GC-HRMS: “Splitless, the PTV injector was held at 90 °C for 0.1 min, ramped to 320 °C at 5 °C/min with a hold time of 5 min” [ 380 ] Pellets of black vulture 4–310 >89 GC-MS/MS: “The GC oven temperature was programmed as follows: initial temperature of 70 °C, hold at 70 °C for 2 min, increase the temperature to 300 °C at ...…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%